Mono Material Lid Film Selection for Ready Meals - Henao Tobon,Ana Maria (2025)
Driven by sustainability goals and regulatory pressure, the packaging industry is transitioning from complex multilayer structures toward mono material solutions that are more easily recyclable. This shift presents challenges, especially in high-performance applications such as microwaveable ready meals, where packaging must endure sealing, cooking, and reheating processes without compromising safety or functionality. This thesis focuses on selecting a suitable mono material polypropylene (PP) lidding film for the Micvac FlexProcess™. A packaging system where food is sealed into a tray, cooked in-pack using microwave energy, and later reheated by the consumer. The lid film plays a critical role by forming a heat-sealable barrier that must expand under steam pressure (ballooning), maintain a vacuum after cooling, and allow safe, user-friendly opening. Its interaction with the tray and valve system is essential for pressure regulation and product integrity throughout the process. To guide evaluation, two design criteria were established: fulfilling product needs such as safety and usability, and meeting process requirements like thermal stability and controlled expansion. These were translated into four critical parameters: sealing performance, pressure resistance, mechanical properties, and peel ability. Five candidate films from three suppliers were assessed through lab and pilot-scale testing. Performance differences were largely influenced by seal layer design and peel mechanisms. A selection matrix based on the Ulrich and Eppinger method enabled structured comparison, identifying M22 as the most promising film, despite some reheating-related limitations. The study concludes with recommendations for further testing using real food products and advanced material characterization to ensure robust performance across the full product lifecycle.
Keywords: Mono material Lid Film; Polypropylene; Microwave Packaging; Critical Parameters; Material Selection Matrix